A study on the influence of training at altitude (2000m) on the maximum aerobic velocity in athletics (mountain race) - Man, M. C.; Ganera, C. (Science, Movement & Health, 2015)
The interest in altitude training is part of the current questions which we must answer in connection with the competitive sport, at the intersection of the adaptation to altitude training and the acclimatization to hypoxia. Objectives: The research aims to achieve a significant increase of sports performance of the athletes practicing athletics, the sports branch -mountain race, by increasing the maximum aerobic velocity (MAV) which is possible by introducing in the training plan a preparatory stage at altitude, after which physiological and biochemical changes occur that are favourable to sustain effort capacity. Methods: The research was carried out on a group of 10 competitive athletes during a training stage of 21 days in the"Piatra Arsã" National Sports Complex of the Bucegi Mountains, situated at an altitude of 2000 m. In order to carry out this research we have used the experimental method, the static-mathematical method and the graphical representation method. For the determination of the MAV (maximum aerobic velocity) and the VO2max (maximum volume of oxygen), the TMI test (le Train Maximal Impose) has been used. Results: The data analysis has shown a significant increase in the maximum aerobic velocity and in the maximum volume of oxygen in terms of performing the training stage at altitude. Conclusions: Performing one or more altitude training stages, significantly improves the aerobic performance of the runners.